Oral Health Status and Associated Factors in a Subpopulation of Turkish Patients - Ahu Dikilitaş; Umut Yiğit; Fatih Karaaslan (Cumhuriyet University, 2019)
Objectives: Understanding the oral health behavior and knowing oral health status of a community in order to facilitate the development of satisfactory dental public health preventive program. In this context, the purpose of this study is to investigate oral health behaviour of Turkish community who live in Usak province besides and to evaluate CPITN and DMFT index scores according to age, gender and education level. Materials and Methods: A face to face questionnaire was conducted for 2412 subjects who were divided into six age groups to understand their oral health behavior. Periodontal measurements, and dental caries were applied by three calibrated expert researchers for all teeth except the third molar. Results: Healthy periodontal tissue only existed in 153 (10.05%) individuals of 1521 dentate participants. The mean DMFT value observed was 16.98±6.62. By aging, being male and having low education level, mean DMFT and CPITN scores showed an upward trend. 10.26% of the participants informed that they did not brush their teeth and 92.55% of them stated that they did not floss their teeth. Most of the participants (83.25%) informed that they visited a dental clinic only in emergency and pain. Conclusions: The mean DMFT and CPITN scores increase in accordance with aging, low education and being male. Low flossing frequency, low prevalence of tooth brushing and low frequency of going to the dentist regularly were observed at the end of the study.